Malezas y su impacto económico en el cultivo de pimiento (Capsicum annuum L.) en el Ecuador - Quinto Espinoza, Lili Selena (2023)
The pepper crop is one of the vegetables whose importance is evident in the high economic index of agricultural production in Ecuador, therefore it represents one of the crops where small, medium and large producers participate. However, currently the integrated management of weeds has become one of the main concerns because the decrease in production has economic impacts, in which damage is reflected, affectations in the physiological and morphological development of the plant causing the decrease of the production. Therefore, among the diversities of weeds, there are gramineous and broadleaf weeds, in such a way that they are configured as a detrimental aspect since their competition for the requirement of nutrients, sun and humidity. In addition, these weeds are hosts for pests and diseases. The intervention of the different weed species has achieved allelopathic effects, causing losses of up to 80% in production. Therefore, promoting correct management and control of weeds is essential, since its execution will help to minimize phytosanitary problems, such as its incidence of economic losses, which is why knowing the type of damage they cause is essential to be able to intercept controls that improve the sustainability of yield and productivity in pepper cultivation.